Evaluasi Alat Ukur Perceived Control pada Konteks Pengerjaan Skripsi menggunakan Confirmatory Factor Analysis - Ilham Phalosa Reswara; Whisnu Yudiana; Surya Cahyadi (Provitae: Jurnal Psikologi Pendidikan, 2021)
Lots of researchers found that perceived control had a major role in various educational activities, including thesis. Unfortunately, there was limited study that validates perceived control inventory to measure the construct, especially in the thesis writing context. The thesis writing context has specific characteristics that make this context unique compare to the general academic context. In order to provide psychometric properties, especially validity evidence in this inventory, the present study aimed to validate the inventory. The research participants (N = 233) were university students from one university and across faculties. Construct validity evidence was used in the present study using Confirmatory Factor Analysis (CFA) to validate the construct. Reliability was also estimated in the study. The result showed that the inventory fulfilled the fit criteria, namely Comparative Fit Index (CFI), Root Mean Square Error of Approximation (RMSEA), Goodness-of-Fit Index (GFI), Normed Fit Index (NFI), and Non-Normed Fit Index (NNFI). The factor loading of each item > .70, the Construct Reliability (CR) of each dimension > .70, and the Average Variance Extracted (AVE) of each dimension > .50. The reliability of the whole construct and its factors also satisfactory (>.70). This result indicated that this inventory was satisfactory in the overall aspect and could be used to measure perceived control in the thesis writing context.